An equivalent uniaxial fatigue stress model for analyzing landing gear fuse pins - Narayan, K.; Behdinan, K.; Vanderpol, P. (Проблемы прочности, 2006)
We study the biaxial stress state conditions in
landing gear fuse pins in the fuse groove. This
biaxial state comprises a combination of shear
stresses which are usually the largest stresses in
the fuse pin by design, and compressive
stresses which keep the half-section of the fuse
pin in equilibrium. Conventional fatigue analysis
techniques use an equivalent uniaxial stress,
based on the Mises stress of a pure-shear condition.
The respective predicted fatigue damages
are much higher than those obtained from fuse
pin cyclic tests. A new equivalent uniaxial fatigue
stress model is proposed that includes the
additional compressive stress as a relief on the fatigue damage in the fuse groove, thereby explaining
the observations from fuse pin tests.
The model is used in conventional uniaxial
strain-life fatigue software (Goodrich Aerospace’s
Fatigue Life V2) to predict the fatigue
damage on a landing gear fuse pin with a sample
load spectrum. The results are then compared
to the pure shear model, and to a biaxial
FEM fatigue analysis. As compared to the
equivalent Mises model, the proposed model
provides less conservative estimation of the
fuse pin fatigue life, the latter value being
higher than that provided by the two-dimensional
FEM calculation. Розглянуто умови двовісного напруженого стану запобіжних елементів шасі -
шплінтів у запобіжних вузлах. У цьому випадку має місце поєднання
дотичних напружень, рівень яких відповідає максимально допустимому
рівню напружень у конструкції, та стискальних напружень, що визначаються
з умов рівноваги. Згідно зі стандартними методиками розрахунку на
утому таке поєднання напружень заміняється еквівалентним одновісним
напруженням на основі умов чистого зсуву по Мізесу. При цьому розрахункові
характеристики матеріалу від утомленості є значно вищими за
експериментальні, що отримані при випробуваннях шплінтів на утому. Запропоновано
модель еквівалентного одновісного утомного напруження, в
якій враховується розвантажувальний ефект стискальних напружень. Модель
використовується в рамках стандартного пакета програм розрахунку
деформаційних кривих утоми (Goodrich Aerospace’s Fatigue Life V2) для
оцінки утомної довговічності запобіжного шплінта шасі під дією циклічного
навантаження. Отримані результати порівнюються з визначеними за допомогою
моделі чистого зсуву і розрахункової скінченноелементної програми.
Використання запропонованої моделі гарантує оцінку утомної довговічності
менш консервативну, аніж за еквівалентною моделлю Мізеса, але більш
завищену порівняно з двовимірним скінченноелементним розрахунком. Рассмотрены условия двухосного напряженного состояния предохранительных элементов
шасси - шплинтов в предохранительных узлах. В этом случае имеет место сочетание касательных
напряжений, уровень которых соответствует максимально допустимому уровню
напряжений в конструкции, и сжимающих напряжений, определяемых из условий равновесия.
Согласно стандартным методикам расчета на усталость такое сочетание напряжений
заменяется эквивалентным одноосным напряжением, исходя из условий чистого
сдвига по Мизесу. При этом расчетные усталостные характеристики материала оказываются
существенно выше, чем экспериментальные, полученные при усталостных испытаниях
шплинтов. Предлагается модель эквивалентного одноосного усталостного напряжения,
в которой учитывается разгрузочный эффект сжимающих напряжений. Модель
используется в рамках стандартного пакета программ расчета деформационных кривых
усталости (Goodrich Aerospace’s Fatigue Life V2) для оценки усталостной долговечности
предохранительного шплинта шасси под действием циклических нагрузок. Полученные результаты
сравниваются с определенными с помощью модели чистого сдвига и расчетной
конечноэлементной программы. Использование предложенной модели обеспечивает оценку
усталостной долговечности менее консервативную, чем эквивалентная модель Мизеса, но
более завышенную, чем двухмерный конечноэлементный расчет.